Transformasi Makna Tradisi Sen Jujur dalam Perkawinan Masyarakat PALI Sumatera Selatan - Aidillah, Elita; Sartika, Diana Dewi; Isyanawulan, Gita; Istiqoma, Istiqoma; Putra, Decka Pratama (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2025)
The Sen Jujur tradition is a vital component of marriage rituals among the PALI community in South Sumatra, symbolizing respect, social responsibility, and the legitimization of familial bonds. However, amid the tide of modernization, these symbolic meanings have undergone a significant transformation. This study aims to explore the shifting meanings of Sen Jujur, from a cultural emblem to an instrument of social prestige and economic burden in contemporary society. Using a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and documentation involving traditional leaders, youth, and families of marriage participants. The findings reveal that Sen Jujur is no longer perceived solely as an expression of honor, but also as a marker of social status, a reflection of women's educational capital, and a site of social negotiation shaped by stratification, patrilocal kinship systems, and the logic of prestige. The study also highlights the practices of Mokon and wedding handshakes (salaman pengantin) as forms of symbolic reciprocity embedded in social exchange systems, as explained in Mauss theory of The Gift. Rather than being a static tradition, Sen Jujur emerges as a dynamic interpretive space continuously negotiated by its actors. This study contributes conceptually to understanding how local traditions adapt, commodify, and respond to social pressures in modern life, while offering a critical reflection on culturally contextualized and sustainable strategies for heritage preservation.AbstrakTradisi Sen Jujur merupakan elemen penting dalam prosesi perkawinan masyarakat Pali, Sumatera Selatan, yang mencerminkan nilai penghormatan, tanggung jawab sosial, serta legitimasi hubungan antar keluarga. Namun, di tengah dinamika modernisasi, makna simbolik tersebut mengalami transformasi signifikan. Penelitian ini bertujuan untuk mengungkap pergeseran makna Sen Jujur dari simbol adat menuju instrumen prestise sosial dan beban ekonomi dalam masyarakat kontemporer. Melalui pendekatan kualitatif-etnografis, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap tokoh adat, generasi muda, dan keluarga pengantin. Hasil penelitian menunjukkan bahwa Sen Jujur tidak lagi dimaknai tunggal sebagai bentuk penghormatan, tetapi juga sebagai alat afirmasi status, simbol kapitalisasi pendidikan perempuan, bahkan arena negosiasi sosial yang dipengaruhi oleh stratifikasi, sistem kekerabatan patrilokal, dan logika gengsi. Temuan juga menyoroti praktik Mokon dan salaman pengantin sebagai bagian dari sistem pertukaran sosial yang sarat makna dan kewajiban timbal balik, sebagaimana dijelaskan dalam teori The Gift (Mauss). Tradisi ini, alih-alih statis, justru menjadi ruang tafsir baru yang terus dinegosiasikan. Studi ini memberikan kontribusi konseptual dalam memahami bagaimana budaya lokal mengalami adaptasi, komodifikasi, serta tekanan struktur sosial dalam kehidupan modern, sekaligus menawarkan refleksi kritis atas strategi pelestarian adat yang lebih kontekstual dan berkelanjutan.